Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

High-Resolution Time-Frequency Feature Enhancement of Bowhead Whale Calls Based on Local Maximum Synchronous Extraction of Generalized S-Transforms - Mingchao Zhu; Rui Feng; Xiaofeng Zhang; Pengsheng Li; Binghua Su (Journal of Marine Science and Engineering, 2025)
Bowhead whales (Balaena mysticetus) are an important species in the Arctic ecosystem, but their conservation is challenged by environmental noise from shipping and climate change. Effective monitoring of Bowhead whale vocalizations is essential for their conservation, yet traditional acoustic methods face limitations in detecting weak and non-stationary signals amidst complex background noise. In this study, we propose a novel method, Local Maximum Simultaneous Extraction of Generalized S-Transforms (LMSEGST), to enhance the feature extraction of Bowhead whale calls. The LMSEGST method integrates generalized S-transforms with local maximum extraction, improving time-frequency resolution and noise immunity. We compare the performance of LMSEGST with traditional methods (STFT, GST, and LMSST) using synthetic and real-world datasets. The results show that LMSEGST outperforms the other methods, with a 28.32% reduction in Rayleigh entropy compared to STFT at 5 dB SNR and a 28.24% reduction compared to LMSST at 10 dB SNR. Additionally, LMSEGST maintained higher SNR values, demonstrating superior noise resistance. These findings suggest that LMSEGST offers a more robust solution for acoustic monitoring of Bowhead whales, particularly in noisy, Arctic environments, contributing to more effective conservation strategies for this species.

Dynamic response and liquefaction mitigation of immersed tunnels under seismic loads: A coupled seawater-seabed-tunnel analysis - Weiyun Chen; Zhiqiang Luo; Lingyu Xu; Yewei Zheng; Lei Su; Rui Huang (Soil Dynamics and Earthquake Engineering, 2025)

Life cycle assessment and economic analysis of integrated biorefinery processes for the production of catechols from catechyl lignin - Lulu Zhan; Shihao Su; Shuizhong Wang; Rui Li; Guoyong Song (Sustainable Chemistry and Pharmacy, 2025)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

Stability and durability of polymeric membranes in membrane bioreactors for industrial wastewater treatment - Qingxian Su; Yijie Zhong; Joceleen Chin Jia Rui; Meiyue Ding; Tze Chiang Albert Ng; Boyan Xu; How Yong Ng (Journal of Environmental Chemical Engineering, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

Effects of inducing conditions on emulsion gel properties of peanut protein isolation-cellulose nanofiber: As extrusion-based 3D food printing inks - Rui Wang; Chun-yan Su; Dong Li; Li-jun Wang (Food Chemistry, 2025)

Effect of freezing-induced pectin degradation on the texture stability of strawberry - Ya Wang; Xuehui Cao; Qianyu Li; Rui Nian; Kaiyan You; Jingkai Su; Xuefeng Xiong; Danshi Zhu (Food Chemistry, 2025)

Advances in enhancing the properties of biodegradable plastics - Rui Chen; Yunhan Li; Jiahuan Ling; Minghai Wang; Can Su; Lihui Zhang (Environmental Research, 2025)

Photo-driven valorization of lactate in human sweat for controllable production of fuels and value-added chemicals - Yu Gao; Rui Zhu; Tengteng Han; Tianran Sheng; Xiaodong Liu; Ming Zhou; Yuchen Ding; Yude Su (Chemical Engineering Journal, 2025)

Cation doping and defects engineering induced NiCoFeP@NC composite as anode for high-performance sodium-ion batteries - Qiangqiang Shi; Shuling Liu; Zhipeng Qin; Xinyue Liu; Xiangxiang Wang; Rui Su; Jianbo Tong (Chemical Engineering Journal, 2025)

Dual-functional 3D-printed polyetheretherketone scaffolds with immunomodulatory nano‑calcium silicate/interleukin-4 coating synergistically enhance osteogenesis through macrophage M2 polarization and NF-κB pathway suppression - Xiaoyu Guo; Yanwen Su; Zixuan Wu; Zidong Wu; Kaili Liu; Junyu Yue; Yuning Qu; Kunzheng Wang; Jiankang He; Rui Ma; Pei Yang (Chemical Engineering Journal, 2025)

Sustainable arsenic stabilization method for hazardous As Ca residues using magnetite tailings and carbide slag for scorodite formation: Implications for harmless treatment and waste reduction - Rui Su; Xuedi Wang; Miao Xu; Yuyin Ma; Yanjiao Gao; Xu Ma; Yubo Cui; Chunxue Bai; Shaofeng Wang (Chemical Engineering Journal, 2025)

Improved nitrogen removal from real mariculture effluent by halotolerant bacterial consortium SND223: Preparation, entrapping application, and mechanism - Xin Su; Shihan Wang; Xiaoqian Cheng; Jing Song; Qing Li; Guixi Yao; Rui Han; Yinghai Wu (Bioresource Technology, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Targeting phosphofructokinase 2 the isoform PFKFB4 suppresses glioblastoma proliferation and malignancy - Eun Bin Lee; Hye Jin Yun; Su Hwan Park; Eun Hee Ko; Young Jun Jung; Rui Liu; Yun-Yong Park; Jong-Ho Lee (Genes & Genomics, 2025)

Leaf-herbivory induced trade-off: Aboveground defense sacrifices root flavonoids to enrich microbes for dual resistance - Junxing Zhang; Chen Ye; Lifen Luo; Yingwei Su; Chenjing Zhao; Yanyan He; Wenjie Luan; Tingshu Yang; Rui Zhang; Bin Chen; Min Yang; Shusheng Zhu (Agriculture, Ecosystems & Environment, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Deep learning approach for internal tide prediction based on China Ocean Reanalysis data - Rui Su; Jun Zhao; Senliang Bao; Hongli Fu; Huizan Wang; Xiaojiang Zhang; Xiang Wang; Can Ma; Weimin Zhang; Xinrong Wu (Ocean Engineering, 2025)

Denitrifying anaerobic methane oxidation reduces greenhouse gas emissions in floodplain sediments of the largest freshwater lake in China under flash drought - Rui Su; Lingtong Zhu; Xiaowei He; Hongjie Zhang; Rui Huang; Jin Zeng; Dayong Zhao (Journal of Environmental Management, 2025)

Characterization and recognition of three-dimensional excitation-emission matrix spectra of wastewater from six typical categories - Litao Kuang; Rui Liu; Meng Jin; Yaqiong Lan; Yingying Su; Yuan Zhao; Lujun Chen (Journal of Environmental Sciences, 2025)

A multiscale peridynamic simulation on thermal-mechanical coupling behavior and damage failure mechanism of granite - Heng Li; Sheng-Qi Yang; Rui Yong; Shi-Gui Du; Bo-Wen Sun; Su-Sheng Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Advanced strategies in organoid/organ-on-a-chip for food safety and nutrition - Yiyan Zhou; Feiran Wang; Rui Zhao; Tianyi Huang; Wentao Su; Ya Wen; Zhixian He; Dong Li (Food Research International, 2025)

Super-hydrophilic/super-hydrophobic composite coating on peripherally inserted central venous catheters for enhanced antifouling, antithrombotic, and antibacterial performance - Haitao Gong; Guochao Zhang; Jian Liu; Chenglei Su; Yanna Ye; Zhihua Gan; Chaoyong Liu; Rui Lian; Qingsong Yu (Chemical Engineering Journal, 2025)

Self-sustaining one-step synergy of ultrasound-enzyme-ethanol for high-efficiency saponin production from waste Xanthoceras sorbifolium leaves - Huan Long; Rui Guo; Wangsheng Zhu; Fuliang Cao; Erzheng Su; Jiahong Wang (Biomass and Bioenergy, 2025)

Protective Effects of Deinoxanthin on Brain Oxidative Damage and Gut Microbiota in the D-Galactose-Induced Aging Mice - Huijuan Su; Yutao Li; Jiayi Wan; Jieyu Lin; Jiayao Wang; Rui Fan; Dingming Liu; Jing Wei; Hongbo Xin; Yuejin Hua; Shengjie Li (Molecular Neurobiology, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

Spatial and Temporal Size Distribution of Swordfish ( Xiphias gladius ) in the Atlantic Ocean: Implications for Conservation and Management - Daniela Rosa; Michael Schirripa; Kyle Gillespie; David Macías; Rodrigo Forselledo; Bruno Mourato; Mikihiko Kai; Freddy Arocha; Nan-Jay Su; Sven Kerwath; Laurent Bahou; Luigi Pappalardo; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Smart weeding system with multi-sensor fusion for tomato plant detection and targeted micro-spraying of intra-row weeds - Jia-Le Li; Wen-Hao Su; Rui Hu; Long-Tao Niu; Qi Wang (Computers and Electronics in Agriculture, 2025)

Vitamin E alleviates ammonia‑nitrogen and hypoxia co-exposure-induced intestinal damage in grass carp (Ctenopharyngodon idella) by modulating mitochondrial function, cellular autophagy and apoptosis - Rui Su; Ke Yao; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Hong-Mei Ren; Xiao-Wan Jin; Pei Wu (Aquaculture, 2025)

Theoretical calculation model of the soil arching effect considering tunnel influence - Rui-Xiao Zhang; Dong Su; Xing-Tao Lin; Xiang-Sheng Chen (Tunnelling and Underground Space Technology, 2025)

An optimal sequential physical retrieval system for retrieving high-accuracy diurnal atmospheric gases from FY-4B/GIIRS: Theory, algorithm and evaluation - Zhenxing Liang; Dasa Gu; Xin Li; Zijie Xu; Xiangyunong Cao; Heming Bai; Rui Li; Chengxing Zhai; Hui Su; Alexis K.H. Lau (Remote Sensing of Environment, 2025)

Sulfur-iron coupled autotrophic denitrification: mechanism of simultaneous nitrogen and phosphorus removal and microbial response characteristics - Rui Zhang; Jinlong Wang; Yongmei Zhang; Su Li; Dingyi You; Zhaoyang You (Journal of Water Process Engineering, 2025)

Diagnostic early freeze onset in the Bering Sea - Weibo Wang; Jie Su; Junpeng Zhang; Rui Ding; Chunsheng Jing; Xiaogang Guo (Journal of Marine Systems, 2025)

A marine fungus Alternaria alternata FB1 degrades polypropylene - Zhenjie Su; Fan Fei; Rui Liu; Chaomin Sun (Journal of Hazardous Materials, 2025)

Constructing MoxTi1-x catalytic pairs to enhance photoelectron transfer for emerging contaminants photocatalytic removal - Hai-Yuan Chi; Jian-bin Su; Sheng-tai Hou; Ze-hua Wang; Xi-tong Li; Wen-long Zhang; Hong-jie Wang; Rui Liu (Journal of Cleaner Production, 2025)

Heteroatom-doped, vinegar residue-derived fluorine/chlorine Co-doped vertical graphene-supported carbon quantum dots as high-efficiency all-carbon electrodes for water electrolysis hydrogen production - Han Yin; Yang An; Chunyu Li; Yu Yan; Rui Su; Chunyang Wan; Bin Jiang; Shanshan Bai; Firdoz Shaik (Journal of Environmental Chemical Engineering, 2025)

Scale effects on buffeting response of long-span bridges - Yi Su; Mingshui Li; Jin Di; Rui Sun; Ming Li; Fengjiang Qin; Yan Jiang; Jie Wang (Engineering Structures, 2025)

Vapor additive strategy enabling perfect crystallization of vacuum-evaporated photovoltaic perovskites - Lei Huang; Zhang Chen; Kai-Li Wang; Zi-Hao Song; Xiao-Ying He; Zhen-Huang Su; Jing Chen; Chun-Hao Chen; Yu Xia; Yu-Tong Yang; Xin Chen; Rui-Hao Qin; et al. (Chemical Engineering Journal, 2025)

Determination of metal(loid) bioavailability in peri-urban agricultural soils and sediments of Southeast China by DGT and probabilistic risk assessment of DGT-derived data - Xihe Yue; Rui-Ze Liang; Richard W. Jordan; Hong Su; Shi-Jun Jiang; Yang-Guang Gu (Journal of Soils and Sediments, 2025)

Endothelial HMGB1-AIM2 axis worsens myocardial ischemia—reperfusion injury by regulating endothelial pyroptosis - Rui Chen; Junying Duan; Ye Zhou; Mengfei Cao; Ye Su; Duzhe Jiang; Aibin Tao; Wei Yuan; Zhiying Dai (Apoptosis, 2025)

An experimental investigation of the performance and pore structure of pervious concrete prepared from waste glass - Qiong Li; Rui Su; Xinyu Shi; Zhanying Huo; Jinlong Jiang; Hongxia Qiao (Minerals Engineering, 2025)

Unveiling the integrated toxicological effects and underlying mechanisms of bisphenol A and cadmium, two hormesis-type endocrine disruptors, on Chromochloris zofingiensis - Rui Feng; Linyuan Song; Haodong Wang; Shixuan Gong; Yangguo Su; Shudong Zhang; Ning Li; Zhao Zhang (Journal of Hazardous Materials, 2025)

Correction to: Effect of Dissolved Oxygen on Poly (3‑Hydroxybutyrate‑co‑3‑Hydroxyvalerate) Solid‑Phase Denitrification: Simultaneous Nitrification and Denitrification Performance and Microbial Community - Peng Zhou; Ying Liu; Xin Su; Peiwu Liu; Rui Han (Water, Air, & Soil Pollution, 2025)

Colletotrichum spaethianum causes leaf spot disease in Stemona japonica in the Guizhou province of China - Rui Zhang; Chengqing Yang; Dengquan Liu; Zhen Su; Zhongshun Cai; Cheng Li (Crop Protection, 2025)

Upcycling of cathode materials from spent lithium-ion batteries cathode materials enabled by deep eutectic solvent - Yanshun Liao; Xianglei Meng; Hongwei Wu; Guang Yang; Xinyao Zhang; Rui Tang; Yali Li; Ni Yang; Yibiao Guan; Yuefeng Su; Feng Wu; Qing Huang (Journal of Environmental Chemical Engineering, 2025)

The feasibility and prospects of coal mine water as a cooling medium for data centers - Zaining Li; Chunhui Zhang; Peidong Su; Guifeng Zhao; ZePeng Wang; YiYun Li; YanXin Li; Mengna Wang; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Chemical Engineering, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Response of carbon flux of alpine ecosystems to hydrological and meteorological factors on the Qinghai-Tibet Plateau - Xiuying Wang; Yuancang Ma; Bingrong Zhou; Fu Li; Shulan Su; Huali Du; Honglu Ma; Shujiao Sun; Haijuan Ji; Rui Zhang (Journal of Mountain Science, 2025)

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Addressing challenges and advancing solutions: Enhancing semi-coking wastewater treatment for a sustainable prospect - Tingting Cui; Chunhui Zhang; Bingxu Quan; Liwei Wang; Zhao Zhang; Peidong Su; Yuanhui Tang; Guifeng Zhao; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Management, 2025)

Cotreatment strategy for hazardous arsenic-calcium residue and siderite tailings via arsenic fixation as scorodite - Rui Su; Xinrong Su; Yanjiao Gao; Xu Ma; Xiaoming Zhao; Xiaoxia Ou; Yubo Cui; Jinru Lin; Yuanming Pan; Shaofeng Wang (Journal of Environmental Sciences, 2025)

The effect of soil microbial functional groups, abiotic and biotic factors on plant functional groups: insights from a tropical rainforest in Southwest China - Yanxuan Chen; Xiaobo Huang; Rong Tang; Rui Zhang; Cong Li; Tongli Wang; Jianrong Su; Shuaifeng Li (Plant and Soil, 2025)

Identifying the Alkaline Tolerance-Related Genes Through Transcriptome Analysis of Halomonas alkalicola CICC 11012 s - Lei Zhai; Shuaicheng Mu; Ruina Liu; Rui Liu; Geer Lin; Qi Han; Su Yao (Current Microbiology, 2025)

How Does Climate Change Influence the Regional Ecological–Social Risks of Harmful Dinoflagellates? A Predictive Study of China's Coastal Waters - Shangke Su; Zhaohe Luo; Jianhua Kang; Xinyuan Guo; Changyou Wang; Rui Jin; Jianguo Du; Xinqing Zheng; Kieng Soon Hii; Shifeng Fu; Wenjia Hu; Bin Chen (Global Change Biology, 2025)
Harmful dinoflagellates are widely distributed in coastal waters worldwide, posing multiple ecological and socioeconomic threats. Climate change may alter the biogeography of these species; however, few studies have linked shifts in harmful dinoflagellates' ecological distribution to their socioeconomic impacts. This study developed a framework to assess the spatiotemporal ecological–social risks posed by harmful dinoflagellates, identifying these algae as risk sources and considering mariculture and coastal populations as the primary risk receptors. China is the world's largest mariculture producer, with approximately 600 million residents living in coastal areas. Focusing on 14 key harmful dinoflagellate species in Chinese coastal waters, we evaluated ecological–social risks under present conditions and two projected climate scenarios for 2100. Our findings indicate that climate change may lead to reductions in suitable habitats for harmful dinoflagellates in tropical and subtropical regions, while habitats in higher‐latitude areas are likely to remain stable or expand. Risk area expansion is projected for four species and increased average risk intensity for three, with two species experiencing both. Nationally, total risk area is projected to remain stable, while cumulative risk intensity may decline by 16.64%. Regionally, risk intensity is expected to rise in northern provinces (up to 30.46%) and decline across most southern provinces. Importantly, we reveal a potential spatial “decoupling” of risk sources and receptors along the coast of China in the future. This decoupling demonstrates a reduced overlap between harmful dinoflagellate distributions and areas with dense mariculture or populations. Our findings suggest that, contrary to the common assumption that climate change universally exacerbates harmful algal impacts, these effects may vary across regions and species, highlighting the importance of localized adaptation strategies in risk assessment. This study provides a robust tool for understanding harmful dinoflagellate risks under climate change, thereby supporting the sustainable management of coastal ecosystems.

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Antifungal activity evaluation of three traditional Chinese herbs against biodeterioration of cultural heritage - Tianxiao Li; Huabing Zhang; Xiang Tan; Rui Zhang; Fasi Wu; Zongren Yu; Bomin Su (International Biodeterioration & Biodegradation, 2025)

Experimental and consolidation modeling of flowing mud during vacuum preloading considering transient clogging and vacuum pressure attenuation - Yuefu Zhou; Rui Chen; Yuanqiang Cai; Jun Wang; Peng Wang; Dong Su; Xiangsheng Chen (Geotextiles and Geomembranes, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

Ionic liquid-grafted MXene composite polymer electrolytes for high-performance solid-state batteries - Zhi Qian; Zhao-Dong Qiu; Rui-Qing Wang; Mei-Tong Wei; An-Min Fei; Zhi-Yi Hu; Hemdan S.H. Mohamed; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Superficial Mycoses: A Mapping Through Bibliometric Research - Jintong Wu; Zijie Tang; Su Wang; Yuxin Qiu; Xinyu Nie; Chengxin Li; Rui Wang (Mycopathologia, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Distinct responses of rare and abundant microbial taxa to long-term soil acidification - Weibing Liu; Rui Yan; Linfa Fang; Hailin Zhang; Haixia Zeng; Wengao Shangguan; Yue Deng; Xiaoxuan Su (Soil Ecology Letters, 2025)

Development of a highly efficient seeding breeding system of Notopterygium incisum - Si Cheng Yao; Qiao Jia Peng; Na Su; Yuan Yuan Jiang; Jin Qiu Liao; Long Wang; Xue Xue Deng; Rui Wu Yang; Xiang Yun Chen; Li Zhang (Plant Biotechnology Reports, 2025)

Exposure to polystyrene nanoplastics causes anxiety and depressive-like behavior and down-regulates EAAT2 expression in mice - Ziyang Su; Rui Kong; Chengqing Huang; Kun Wang; Chenhao Liu; Xiaozhen Gu; Hui-Li Wang (Archives of Toxicology, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Effects of starvation-refeeding on antioxidant status, metabolic function, and adaptive response in the muscle of Cyprinus carpio - Wenrong Feng; Jianlin Li; Yuanfeng Xu; Gang Jiang; Shengyan Su; Zhihua Zhang; Rui Jia; Yongkai Tang (Aquaculture, 2025)

Multi-layer landscape design of urban spontaneous plant community: A case study in Zhengzhou, China - Wangxin Su; Zeqi Zhai; Wenhui Zhang; Rui Li; Jiayi Li; Yang Liu; Wenqian Jiang; Hong Wei; Nan Guo; Yonghua Li (Urban Forestry & Urban Greening, 2025)

Removal of arsenic from water by silver nanoparticles and Fe-Ce mixed oxide supported on polymeric anion exchanger - Li Li; Su-juan Yu; Rong-gang Zheng; Qing-cun Li; Rui Liu; Jing-fu Liu (Journal of Environmental Sciences, 2025)

The role of defatted hydrolyzed egg yolk powder in protecting DHA algal oil - Yingxin Wei; Huan Rui; Xuechun Wang; Cuihua Chang; Yi Wang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Chemistry, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Structural characteristics and anti-tumor activities of a novel polysaccharide from Klebsiella sp. SXW12 - Xiaqing Sun; Zhenxuan Wei; Yawen Su; Rui Fang; Yizhuo Fan; Dejie Zeng; Qiankun Ding; Yaqiong Miao; Junhao Liu; Qi Sun (Carbohydrate Polymers, 2025)

Monthly variations of the spring greenness response across boreal Eurasia to the preceding wintertime northern annular mode during 1982–2022 - Jing Li; Weiming Zeng; Ruichen Lin; Zhiqing Xu; Xilin Xie; Feng Su; Rui Zhao; Anmin Duan (Climate Dynamics, 2025)

Salinicoccus bachuensis sp. nov., a novel halophilic bacterium, isolated from rhizosphere soil surrounding Tamarix chinensis Lour. plants in Bachu County, Xinjiang, China - Zhen-Pu Liang; Rui Wang; Han-Wen Cao; Xin-Lu Zhou; Jin-Ping Dai; Ping Su; Deepali Singh; Xiao-Xia Zhang (Archives of Microbiology, 2025)

Based on NRCS and the Doppler centroid anomaly in SAR images to retrieve the nearshore bathymetry - Rui Qi; Jiamin Lin; Jian Wang; Xiaonan Yao; Xiaoqing Wang; Xinzhe Yuan; Lei Cui; Peiqing Yang; Xingyi Su (International Journal of Remote Sensing, 2025)

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Dissimilatory nitrate reduction pathways drive high nitrous oxide emissions and nitrogen retention under the flash drought in the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Hongjie Zhang; Junxiang Cheng; Ligang Xu; Qinglong L. Wu; Jin Zeng (Water Research, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

ANAC050 confers aluminium resistance by cooperating with secretion of organic acids and accumulation of cell wall hemicelluloses in plants - Ye TAO; Su LI; Yusong LIU; Rui GUO; Changzhao CHEN; Jiu HUANG; Qiang ZHANG; Renfang SHEN; Xiaofang ZHU (Pedosphere, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Spatio-temporal variability of surface phytoplankton community structure in relation to different water systems in the east China sea coast - Anglu Shen; Shuaishuai Su; Haowen Li; Wei Kang; Rui Jia (Continental Shelf Research, 2025)

Dynamic characterization of the changes in intestinal fungi and fecal metabolites during the reproductive cycle of sows - Jin-Wen Su; Xin-Wen Hou; Shuo Liu; Yu Chen; Ji-Xin Zhao; Xiao-Xuan Zhang; Hong-Bo Ni; He Ma; Rui Liu (Veterinary Research Communications, 2025)

Coastal redox shifts over the past 167 years and preservation of total organic carbon and total nitrogen - Yang-Guang Gu; Hai-Song Li; Hong Su; Richard W. Jordan; Rui-Ze Liang; Shi-Jun Jiang (Marine Pollution Bulletin, 2025)

Tibetan Plateau palm fossils prove the Kohistan-Ladakh Island Arc is a floristic steppingstone between Gondwana and Laurasia - Yi Gao; Ai Song; Wen-Jian Cai; Robert A. Spicer; Rui Zhang; Jia Liu; Gaurav Srivastava; Xuan-Rong Yao; Xing-Yuan Qin; Hao Tang; Shu-Feng Li; Tao Su (Review of Palaeobotany and Palynology, 2025)

A path-dependence aware LSTM-based framework for modeling the mechanical behavior of unsaturated soil - Guoqing Cai; Yongjian Liu; Rui Yang; Yanlin Su (Computers and Geotechnics, 2025)

Corrigendum to “Chargeable persistent luminescence 3D-printed scaffolds: A stepwise tactic for osteosarcoma treatment” [Chem. Eng. J. 479 (2024) 147436] - Rui Huang; Ni Ni; Yun Su; Li Gu; Yahan Ju; Dandan Zhang; Jipeng Li; Meiqi Chang; Yu Chen; Ping Gu; Xianqun Fan (Chemical Engineering Journal, 2025)

Zinc-doped nickel sulfide/nickel hydroxide heterostructures for efficient and robust selective glucose oxidation reaction - Chi Zhang; Chunjian Xu; Linrui Yang; Xinyue Tao; Jianyi Liu; Rui Su; Xiangjun Meng; Ruoxi Yang; Dongfang Xue; Kaitian Zheng (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

Experiment and Peridynamics Simulation on Failure Mechanical Behavior of Cylindrical Sandstone Containing Two Persisting Fissures Under Conventional Triaxial Compression - Sheng-Qi Yang; Heng Li; Shi-Gui Du; Rui Yong; Su-Sheng Wang; Wen-Ling Tian; Yun-Jin Hu; Yong Niu (Rock Mechanics and Rock Engineering, 2025)

Computational Design and Optimization of Multi-Compound Multivesicular Liposomes for Co-Delivery of Traditional Chinese Medicine Compounds - Mengjie Rui; Yali Su; Haidan Tang; Yinfeng Li; Naying Fang; Yingying Ge; Qiuqi Feng; Chunlai Feng (AAPS PharmSciTech, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Effects of microclimatic conditions and urban building configurations on aerodynamic characteristics and health risks of bioaerosols: Insights from idealized urban models - Zhijian Dong; Zhijian Liu; Chenxing Hu; Chenglin Ye; Yongjun Jin; Haiyang Liu; Rui Rong; Yuchen He; Li Chen; Chuanchen Li; Yaolong Shi; Yufeng Su (Sustainable Cities and Society, 2025)

Ultrafast and ultrastable Na-ion storage in interface engineered MoS2/MXene nanohybrids with nanoconfinement for high-performance sodium-ion capacitors - Yuanhua Xiao; Qingling Le; Yang Kong; Wendi Lv; Dangcheng Su; Xianhong Rui; Shuyan Yu; Aiqing Zhang; Junhong Zhao; Qingxiang Yang; Qingxian Jin; Yujie Zheng; et al. (Chemical Engineering Journal, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

The impact of natural disasters on stock market participation in urban China - Rui Zhang; Zheyu Lin; Yiming Su; Xinghan Zhu; Huijuan Wang (Environment, Development and Sustainability, 2025)

Thermo-responsive Fluorescent Nanopolymer Delivery Platform for Treatment of Diffuse Large B-cell Lymphoma (DLBCL) - Yun Lin; Rui Su; Yun Huang (Journal of Fluorescence, 2025)

Corrigendum to “Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs” [Aquaculture Volume 594, 15 January 2025, 741341] - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Intestinal flora analysis and serum metabolomics reveal the effectiveness of Bacillus coagulans BC66 in treating bacterial enteritis in bullfrogs - Zehui Su; Fu Gao; Rui Shu; Kai Cai; Shuguang Fang; Xiaoting Lei; Dan Li; Kun Hu (Aquaculture, 2025)

Over 200 times current enhancement via buckling triboelectric nanogenerator at ultra-low speed for monitoring the swelling of lithium ion batteries - Maoyi Zhang; Chaosheng Hu; Tongtong Zhang; Chris R. Bowen; Rui Li; YongAn Huang; Yewang Su; Zhong Lin Wang; Ya Yang (Science Bulletin, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

A facile colorimetric sensor for ketoprofen detection in milk: Integrating molecularly imprinted polymers with Cu-doped Fe3O4 nanozymes - Yu Su; Xinjie Yin; Xiaofeng Wei; Rui Xu; Liwen Wei; Yanhua Chen; Lan Ding; Daqian Song (Food Chemistry, 2025)

Molecular level modulation of anthracite-based hard carbon precursors for efficient sodium-ion batteries - Rui Li; Chunbo Su; Wei Yang; Ruizhe Xu; Kai Chen; Jian Chen; Wei Su; Beilei Yuan; Jianping Long; Anjun Hu (Chemical Engineering Journal, 2025)

Impact of Tonga volcanic eruption on the ionosphere based on ground-based GNSS and COSMIC occultation data - Xiaoxiao Chen; Rui Zhang; Xiangyu Kong; Zhanwen Liang; Lina Su; Changwei Wang (Advances in Space Research, 2025)